Literature Review Riset Literasi Perbankan Syariah Indonesia - Wahyudin Darmalaksana; Widodo Dwi Ismail Aziz; Mahmud Mahmud (Gunung Djati Conference Series, 2022)
This study aims to conduct a literature review of the results of research on Islamic banking literacy. This study uses a qualitative approach by applying the descriptive-analytical method. The results of this study indicate that several research results confirm the urgency of literacy, religiosity, and Islamic branding of Islamic banking. The results of the discussion explain that literacy, religiosity, and Islamic branding have a positive effect on people's perceptions of the use of Islamic financial services, but religiosity is not significant compared to the influence of Islamic branding. This study concludes that literacy levels have a significant effect on people's perceptions of the use of Islamic banking financial services. This study recommends Islamic banking institutions to carry out strategic cooperation, especially with Islamic higher education institutions in implementing the agenda of strengthening public literacy for Islamic banking industry products in Indonesia.